PEMBUATAN VIDEO MAKANAN KHAS JAWA TIMUR - Rapha Natanael; Melissa Angga; Ongko Citrowinoto (Perpustakaan Universitas Surabaya, 2018)
Regional cuisines are commonly consumed food in an area and match the tongue of the local community. The sustainability of regional cuisines is very important for a region to boost its tourism sector. The onslaught of modernization and globalization threatens the preservation of regional cuisines, especially in East Java. Over time, these cuisines is increasingly potentially neglected by the next generation. If they are not used to eat these foods, consequently these cuisines will be reduced and even lost its existence. East Java cuisines need to be reintroduced to the young generation. With the problem mentioned, come an idea to make a video about East Java cuisines to re-appeal to the younger generation. Through various analyzes conducted, found some regional foods of East Java which began to be forgotten by the younger generation. In addition, some there are some requirements of the video to be made. Video is designed and conceptualized with the theme of traveling. The title used for this video series is